Nystatin changes the properties of transporters for arginine and sugars. An in vitro study - Opekarová, M; Tanner, W (FEBS letters, 1994)
In ergosterol-containing energized yeast plasma membrane vesicles nystatin (5-10 micrograms/mg total lipid) caused a massive efflux of pre-accumulated arginine while the membrane potential (the principal driving force; -110 mV) decreased by only 10-30 mV. Neither the substrate fluxes nor the membrane potential was influenced by nystatin when the permease was reconstituted in ergosterol-free phospholipid vesicles. The same effect of nystatin was found with the reconstituted sugar transporter from Chlorella kessleri. It is suggested that nystatin binding to ergosterol in the vicinity of the permease releases the transport protein from its coupling to energy and converts it to a facilitator.
Keywords: arginin; buněčná membrána; transportní proteiny; Saccharomyces cerevisiae; Arginine; nystatin; Carbohydrate Metabolism; Carrier Proteins; biologický transport; Cell Membrane; Membrane Potentials; Nystatin; membránové potenciály; metabolismus sacharidů; Biological Transport